Students’ Conceptual Understanding in Probability: A Qualitative Analysis Based on Mathematics Anxiety Levels within the Missouri Mathematics Project Approach - Fitriyani, Dea; Agrestian, Rizki (Al-Mufid, 2024)
This study aims to analyze students’ conceptual understanding in probability based on their levels of mathematics anxiety through the implementation of the Missouri Mathematics Project (MMP) learning model. A qualitative descriptive approach was employed, involving six students from SMA IT At-Tadzkir who were selected using stratified purposive sampling based on low, moderate, and high levels of mathematics anxiety. Data were collected through anxiety questionnaires, mathematical concept understanding tests, and semi-structured interviews. The test instrument was developed using five indicators of conceptual understanding, including verbal restatement, classification, algorithmic application, representation, and conceptual connection. The findings indicate a strong relationship between mathematics anxiety and students’ conceptual understanding. Students with low anxiety levels demonstrated mastery across all five indicators, showing confidence and logical reasoning in their responses. Those with moderate anxiety showed partial mastery, often hesitating when confronted with complex tasks. In contrast, students with high anxiety levels struggled with most indicators and displayed signs of emotional discomfort during the interview process. These results suggest that mathematics anxiety significantly impacts students' ability to comprehend mathematical concepts, and that the MMP model, while effective, requires additional affective support to optimize learning outcomes.